Clinical assessment and diagnosis in social work practice - Corcoran, Jacqueline (Oxford University Press, 2006)
"Guides social workers in developing competence in the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR) system of diagnosis, and assists them in staying attuned during client assessment to social work values and principles"--Provided by publisher.